Early Magnetic Resonance Detection of Natalizumab-Related Progressive Multifocal Leukoencephalopathy in a Patient with Multiple Sclerosis. (10th March 2013) - Manenti, Guglielmo; Altobelli, Simone; Nezzo, Marco; Antonicoli, Marco; Vasili, Erald; Neroni, Luca; Floris, Roberto; Simonetti, Giovanni
Abstract : Diagnosis of progressive multifocal leukoencephalopathy is usually based on the clinical presentation, on the demonstration of the brain lesions at the magnetic resonance imaging examination, and on the detection of the JC virus DNA in the cerebrospinal fluid with high sensitive polymerase chain reaction. The role of magnetic resonance imaging specifically in natalizumab-associated progressive multifocal leukoencephalopathy is strengthening, and it is gaining importance not only as an irreplaceable diagnostic tool but also as a surveillance and risk stratifying tool in treated patients. While other imaging techniques such as computed tomography lack sensitivity and specificity, magnetic resonance performed with morphological and functional sequences offers clinicians the possibility to early identify the stage of the disease and the emergence of an immune reconstitution inflammatory syndrome after natalizumab blood removal plasmapheresis.